Phylogeography of the freshwater red alga Batrachospermum viride-brasiliense (Rhodophyta, Batrachospermales) - Paiano, Monica O. [UNESP]; Necchi, Orlando [UNESP] (Wiley-Blackwell, 2017)
Phylogeography of Batrachospermum viride-brasiliense was investigated using two mitochondrial regions: the cox2-3 spacer and the barcode region of cox1 gene. Eighty-seven individuals were analyzed from nine stream segments throughout its distribution in Brazil. Ten cox2-3 spacer and nine cox1 haplotypes were observed among the individuals studied (87 vs. 43, respectively). Divergences among haplotypes were relatively low (<= 2.4% for cox2-3 and <= 1.8% for cox1). Most locations have a single haplotype, whereas only two locations had two haplotypes for both markers. The haplotype network for cox2-3 showed a phylogeographic trend from the south towards the southeast with haplotypes from the southeast more closely related. For cox1 a trend from the southeast spreading towards the south and north was revealed, with the southern haplotypes more closely associated. Results clearly indicated that B. viride-brasiliense represents a single species and the phylogeographic pattern consisted of a closely connected group of haplotypes from southern and southeastern Brazil. Levels of intra-and inter-population variation were similar for the two markers with slightly higher values for cox2-3. The trend observed in this study is similar to that in other members of Batrachospermales with little variation within a stream segment (one or two haplotypes) and more distant haplotypes showing higher divergences. This pattern could be attributed to the fact that colonization of a site might be rare by a single event with subsequent proliferation of the population. The geographic distribution of B. viride-brasiliense was interpreted according to the biogeographic models proposed for South America being limited to three morpho-climatic domains or biogeographic provinces: tropical Atlantic rainforest, sub-tropical rainforest and cerrado (Brazilian savannah).
Keywords: Batrachospermum; cox1; cox2-3 spacer; genetic diversity; geographic distribution; intra-specific variation